Improving risk assessment of chemicals by the use of human biomonitoring: HBM4EU project activities - Santonen, T. (2018)
The default approach in the risk assessment (RA) of chemicals is to assess external exposure by combining different sources and routes of exposure. This kind of approach contains various uncertainties and may overestimate exposure, since conservative estimates are needed due to the limited data on, for example, the absorption of the chemical and interspecies and intraspecies differences. Human biomonitoring (HBM) can help improve RA by providing measured data on combined exposures. In some cases, biomonitoring data can even provide a direct link to health effects. In some cases, biomonitoring allows to link exposure to specific contexts such as occupational settings. Although recent years have seen good examples of the use of biomonitoring in the risk assessment of chemicals, much work is still needed to improve its use in regulatory RA and human impact assessment (HIA). The European Human Biomonitoring Initiative (HBM4EU) was recently launched for fulfilling the gap between the exposure to hazardous chemical agents and their impact on human health. One of the aims of the HBM4EU project is to enhance the use of HBM data in RA and HIA of chemicals in different regulatory contexts including legislation on chemicals, plant protection products, and biocides, as well as legislation on cosmetics, food safety, and occupational safety. RA models for mixtures are also considered. Firstly, current RA practices are evaluated: is the use of biomonitoring integrated with the available RA guidance, and do give RA schemes have good examples of the advanced use of biomonitoring? A survey is also conducted to gather information from national regulatory risk assessors (in the EU, but also in non-EU countries) on their risk assessment practices, the use of HBM, and the obstacles and challenges related to its use. The challenges of the use of HBM data in RA may include a lack of guidance in the use of biomonitoring, a lack of knowledge regarding the interpretation of biomonitoring results, or the inability to link biomonitoring data to different exposure sources. Using a selected group of priority chemicals as an example, we can determine whether these challenges can be overcome by including the recent HBM data, collected during the HBM4EU project, in the existing RA schemes. Finally, proposals will be made for the better use of HBM in RA and HIA in different policy domains.